see the attached figure to better understand the problem
we have that
![cos(A)=\frac{1}{5} \\ AB=12\ units\\ CD=2\ units](https://tex.z-dn.net/?f=cos%28A%29%3D%5Cfrac%7B1%7D%7B5%7D%20%5C%5C%20AB%3D12%5C%20units%5C%5C%20CD%3D2%5C%20units)
Step 1
<u>Find the value of AC</u>
we know that
in the right triangle ABC
![cos (A)=(AC/AB)\\AC=AB*cos(A)](https://tex.z-dn.net/?f=cos%20%28A%29%3D%28AC%2FAB%29%5C%5CAC%3DAB%2Acos%28A%29)
substitute the values in the formula
![AC=12*(1/5)\\ AC=2.4\ units](https://tex.z-dn.net/?f=AC%3D12%2A%281%2F5%29%5C%5C%20AC%3D2.4%5C%20units)
Step 2
<u>Find the value of BC</u>
we know that
in the right triangle ABC
Applying the Pythagorean Theorem
![AB^{2} =AC^{2}+BC^{2}\\ BC^{2}=AB^{2} -AC^{2}](https://tex.z-dn.net/?f=AB%5E%7B2%7D%20%3DAC%5E%7B2%7D%2BBC%5E%7B2%7D%5C%5C%20BC%5E%7B2%7D%3DAB%5E%7B2%7D%20-AC%5E%7B2%7D)
substitute the values
![BC^{2}=12^{2} -2.4^{2}\\BC^{2}= 138.24\\ BC=11.76\ units](https://tex.z-dn.net/?f=BC%5E%7B2%7D%3D12%5E%7B2%7D%20-2.4%5E%7B2%7D%5C%5CBC%5E%7B2%7D%3D%20138.24%5C%5C%20BC%3D11.76%5C%20units)
Step 3
<u>Find the value of BD</u>
we know that
in the right triangle BCD
Applying the Pythagorean Theorem
![BD^{2} =DC^{2}+BC^{2}](https://tex.z-dn.net/?f=BD%5E%7B2%7D%20%3DDC%5E%7B2%7D%2BBC%5E%7B2%7D)
substitute the values
![BD^{2} =2^{2}+11.76^{2}](https://tex.z-dn.net/?f=BD%5E%7B2%7D%20%3D2%5E%7B2%7D%2B11.76%5E%7B2%7D)
![BD=11.93\ units](https://tex.z-dn.net/?f=BD%3D11.93%5C%20units)
therefore
<u>the answer is</u>
the length of BD is 11.93 units
1. 18,000 x 1.03 (3% increase) either type 1.03 into your calculator 25 times or use an exponent ↓↓↓↓↓↓↓
18000 x 1.03^25 (25 years past) =37,688.00
Answer:
± 60
Step-by-step explanation:
aₙ = a₁ * rⁿ⁻¹
a₇ = 30 = a₁ * r⁷⁻¹ = a₁ * r⁶ (1)
a₅ = 120 = a₁ * r⁵⁻¹ = a₁ * r⁴ (2)
(1)/(2): 30/120 = 1/4 = r²
r = ± 1/2 or ± 0.5
a₁ = a₇/r⁶ = 30/0.5⁶ = 1920
a₆ = 1920 * (± 1/2)⁶⁻¹ = 1920 * ± 1/32 = ± 60
Answer:
89 degrees
Step-by-step explanation:
6 pi 10m divided by 35. The rombos formla.
Answer:
<u><em>14</em></u>
<u><em></em></u>
Step-by-step explanation:
<u><em> Expression: Negative × Negative + Positive </em></u>
<em><u>Product: Positive </u></em>
<u><em>Answer: (-3 × -2) + 8 .</em></u>
<em> 6 + 8 = 14</em>
<em> 14</em>